The Influence of Knowladge and Atitudes on the Implementation of End of Life Care among Nurses in the Emergency Room and Intensive Room - Alvareza Ratih Damayanti, Anastasia; Koerniawan, Dheni; Frisca, Sanny (Catholic University Musi Charitas, 2024)
fff